2000
DOI: 10.1111/j.1744-7429.2000.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dispersal Pattern and Mammalian Herbivores on Seedling Recruitment for Virola michelii (Myristicaceae) in French Guiana1

Abstract: The effects of dispersal pattern (seeds in small clumps vs. seeds scattered in pairs) and distance to the nearest Carapa procera (Meliaceae; a tree that produces seeds preferred by terrestrial vertebrates) on survival of seeds and seedlings were examined for the animal–dispersed tree species Virola michelii (Myristicaceae) in a mature forest‘at Paracou, French Guiana, in 1992 and 1993. We assessed the putative role of ground–dwelling mammalian herbivores, rodents, and ungulates that filter the seed shadow, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Forget et al (2000) found that in the short term (6 weeks), clumped seeds of Virola michelii had a higher probability of survival than did scattered seeds, but that no such difference remained after 1 year. Our results indicate that a similar process may be operating in Dipteryx.…”
Section: Density Dependencementioning
confidence: 86%
“…Forget et al (2000) found that in the short term (6 weeks), clumped seeds of Virola michelii had a higher probability of survival than did scattered seeds, but that no such difference remained after 1 year. Our results indicate that a similar process may be operating in Dipteryx.…”
Section: Density Dependencementioning
confidence: 86%
“…Due to their biomass in the ecosystem and dietary preferences, T. pecari are likely to have an essential, although poorly understood, role in altering the seed shadow of large seeded tree species. T. pecari are quickly eliminated in the presence of human inhabitants (Peres 1996) and most Amazonian seed predation studies have been conducted in areas with reduced T. pecari populations (Burkey 1994;Notman et al 1996;Forget et al 2000).…”
Section: Mammalian Seed Predatorsmentioning
confidence: 99%
“…The Janzen-Connell model predicts that seed predators will exert greater predation pressures where dispersed seeds are densest or closest to a reproductive conspecific. Distance-or densitydependent mortality during recruitment leads to a decreased probability that a species will replace itself at a site and promotes maintenance of diversity (Janzen 1970;Augspurger 1984;Clark and Clark 1984;Howe 1989;Forget et al 2000). The Janzen-Connell predictions have been studied intensively, but most studies have been conducted in areas without a full complement of large mammals (Wright 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Janzen's model predicts an enhancement of seed predation rate according to seed density or proximity to a reproductive tree. Distance-or density-dependent mortality during recruitment leads to a decreased probability that a species will replace itself at a site and promotes maintenance of diversity (Janzen, 1970;Clark and Clark, 1984;Forget et al, 2000). In fact, seed predation may be either positively or negatively densitydependent and the pattern can be expected to vary with the relative abundance of seeds and their predators.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a canopy or a collection of neighboring canopies bearing enhanced fruit crop sizes tend to cause predator satiation, which consequence is an improved seed survival within a dense seed patch (Augspurger, 1981;Ghazoul and Satake, 2009). Therefore, seed success is strongly influenced by pre-dispersal seed predators, and negative density-dependent effect on seed predation or predator satiation will determine the fecundity level of individual plants (Forget et al 2000;Ghazoul and Satake, 2009).…”
Section: Introductionmentioning
confidence: 99%